Analisis Perbandingan Mesin Render Redshift, Arnold Renderer, Maya Hardware 2.0 Pada Shot Indoor Dan Outdoor Di Dalam Kondisi Siang Dan Malam Pada Animasi 3d “Telat” - Hasil Bangun Taras Barus; Riwinoto Riwinoto; Prananda Justis (Politeknik Negeri Batam, 2021)
The development of computer graphics technology in Indonesia continues to grow, especially in the 3D animation film industry. In the process of making 3D animated films Some steps that must be done are, Modeling, Texturing, Rigging, Animating, Lighting Setup, and Rendering. At the rendering stage, it is often found that the time and quality problems produced on each existing rendering machine are because each rendering machine has a great importance to the time and quality produced. It is expected to choose the right rendering engine in the production process of 3D animated films so it is necessary to do research to understand the rendering engine with the best image quality and the rendering engine with the fastest rendering time by using facts and facts related to indoor and outdoor in conditions of day and night . The study was conducted by rendering on 3 rendering machines namely redshift, Arnold Renderer, and Maya Hardware 2.0 on the 3D animation film